Growth and yield of lettuce cultivars under organic fertilization and different environments - Silva, Alisson Franco Torres da; Avelino, Rodrigo Cirqueira; Brito, Leonardo Pereira da Silva; Anjos, João Carlos Rocha dos; Silva Júnior, José Valdenor da; Beckmann-Cavalcante, Márkilla Zunete (Comunicata Scientiae, 2018)
Lettuce (Lactuca sativa L.) is a leafy vegetable that could be grown under mineral or organic fertilizing, being also very influenced by environmental conditions. This study evaluated the growth and yield of lettuce cultivars submitted to different doses of organic fertilization and environmental conditions. The experiment was carried out at the Horticulture Sector of the Campus Cinobelina Elvas, at the Federal University of Piauí (CPCE/UFPI), Brazil. The experimental was carried out in a completely randomized block design, with the treatments distributed in split-split-plot, according to cultivation systems in the plots (with 50% of shading and outdoor cultivation), organic fertilization rates in subplots (0, 20, 40, 60 and 80 t ha-1) and lettuce cultivars in the sub-subplots (‘Delícia’, ‘Babá de Verão’ and ‘Itapuã 401’) with three repetitions and with eighteen plants per experimental unity and four useful plants per plot. Plant height, number of leaves, head circumference, stem length, leaf area, leaves chlorophyll content, commercial fresh mass, shoot dry matter and lettuce yield were evaluated. For the conditions in which the present study was carried out, the use of doses of organic fertilization with cattle manure influenced lettuce growth and yield using 50% of shading and is also suggested the use of the cultivars ‘Delícia’ and ‘Babá de Verão’, in a protected environment (50% of shade).